2011
DOI: 10.1107/s1744309110051523
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and preliminary X-ray crystallographic study of a methyltransferase involved in 2-methylisoborneol biosynthesis inStreptomyces lasaliensis

Abstract: The biosynthetic pathway of the off-flavour terpenoid alcohol 2-methylisoborneol (2-MIB) requires geranyl pyrophosphate methyltransferase (GPPMT) to methylate GPP before the cyclization reaction. GPPMT is the first example of an S-adenosyl-L-methionine-dependent methyltransferase that acts on general intermediates such as geranyl pyrophosphate and farnesyl pyrophosphate in isoprenoid biosynthetic pathways. In this study, recombinant GPPMT was overproduced, purified and crystallized in the absence and presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The procedures used to prepare the proteins and crystals have been described previously (Ariyawutthiphan et al, 2011). We used three types of crystals in this study, i.e.…”
Section: Structure Determinationmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedures used to prepare the proteins and crystals have been described previously (Ariyawutthiphan et al, 2011). We used three types of crystals in this study, i.e.…”
Section: Structure Determinationmentioning
confidence: 99%
“…apo, a complex with SAM and a tertiary complex with both SFG and GPP (hereafter called the substrate complex), to analyze how this enzyme recognizes the substrates and its reaction mechanism. Methods for solving the structures have previously been published (Ariyawutthiphan et al, 2011); the data-collection, processing and structure-refinement statistics are summarized in Table 1. All data sets were integrated, merged and scaled using HKL-2000 (Otwinowski & Minor, 1997).…”
Section: Structure Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…The preliminary X-ray crystallographic analysis of the S. lasaliensis 2-MeGPP synthase has recently been reported. 41 A new profile HMM for the region around two conserved metal-binding motifs of microbial terpene synthases also identified a single open reading frame of 397 aa within the genome sequence of the cyanobacterium, Pseudanabaena limonetica . 42 Heterologous expression of the corresponding gene product has confirmed the identity of the cyanobacterial 2-methylisoborneol synthase as well as the coupled 2-MeGPP synthase.…”
Section: Case Studiesmentioning
confidence: 99%
“…Together, these structures provide important clues regarding the mechanism of the unusual isoprenoid methylation reaction catalyzed by GPPMT. Although these are the first structures of an isoprenoid methyltransferase to be reported in the Protein Data Bank (www.rcsb.org), we note that the crystallization and preliminary X-ray crystallographic study of GPPMT from Streptomyces lasaliensis was recently reported (24). …”
mentioning
confidence: 95%